Makna Mendidik pada Kriya Songket Silungkang Sumatera Barat - Budiwirman Budiwirman (PANGGUNG, 2012)
ABSTRACTOne of the handicraft products related to Silungkang ceremony in West Sumatra is woven songket. This study is aimed at documenting the indigenous culture of Minangkabau which is closely linked to the existence of weaving/songket Silungkang, and reviewing the various motives of songket in the same way as the language which is used as a tool of communication. This type of research is closely linked with the methods of ethnography, then it is processed through a qualitative description. The result of the research shows that songket attire is a symbol of the livelihood of indigenous people in the value of educating people and is used for all forms of ceremonial pomp (ceremonial). Therefore, the motives of songket have a strong position as a means of communication, for a variety of motives with their meanings are part of the indigenous institutions that must be obeyed.Keywords: Symbol, Songket, CultureABSTRAKSalah satu produk kerajinan yang terkait dengan upacara Silungkang di Sumatera Barat adalah tenunan songket. Penelitian ini bertujuan untuk mendokumentasikan budaya asli Minangkabau yang terkait erat dengan keberadaan tenun/songket Silungkang, dan mengkaji berbagai motif songket dengan cara yang sama sebagaimana bahasa yang digunakan sebagai alat komunikasi. Jenis penelitian ini berhubungan erat dengan metode etnografi, maka penelitiannya diproses melalui deskriptif kualitatif. Hasil penelitian menunjukkan bahwa pakaian songket merupakan simbol dari kehidupan masyarakat adat dalam hal mendidik masyarakat dan digunakan untuk semua bentuk kemegahan upacara (seremonial). Oleh karena itu, motif songket memiliki posisi yang sangat kuat sebagai sarana komunikasi karena berbagai motif dengan maknanya masing-masing merupakan bagian dari adat istiadat yang harus dipatuhi.Kata kunci: simbol, songket, budaya